Agency development and valuing peer perspectives: lessons from an intervention to enhance STEM university students’ feedback literacy - Hui,L; Ippolito,K; Charalambous,M (Teaching & Learning Inquiry: The ISSOTL Journal, 2025)
In order for students to benefit from feedback, they must develop their feedback literacy. To investigate the extent to which informing students about feedback knowledge and scaffolding practice for making sense of feedback increases feedback literacy, we conducted a skills-based intervention study. The results showed that the intervention increased students’ feedback knowledge, that is, their understanding about the purpose of feedback and the need to engage with it proactively. However, the intervention did not increase participants’ feedback literacy to a statistically significant extent. This may be due to the centrality of learner agency in feedback literacy and lack of time for this complex construct to develop. Findings from post-intervention focus group interviews revealed variation in students’ understanding and agency in relation to engaging with feedback and the importance of including various opportunities to develop agency as part of feedback literacy training, including through peer perspective sharing. Cultural influences on feedback processes appeared to be less significant than anticipated. Instead, individual differences, such as personal interpretations of feedback and associated emotional responses, were more likely to create barriers, and should therefore be considered when developing feedback literacy. This paper offers suggestions for implementing more effective feedback literacy development opportunities, including those that emphasise building on a foundation of feedback knowledge and the role of peers and peer feedback. We propose that future studies should develop an integrative approach to feedback literacy training that acknowledges the complexity and time demands of agency development.